Observation of the decay B0s→[eta]c[phi] and evidence for B0s→ [eta]cπ+π− - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; et al. (Journal of high energy physics, 2017)
A study of B s 0 → η c ϕ and B s 0 → η c π + π − decays is performed using pp collision data corresponding to an integrated luminosity of 3.0 fb−1, collected with the LHCb detector in Run 1 of the LHC. The observation of the decay B s 0 → η c ϕ is reported, where the η c meson is reconstructed in the pp¯¯¯pp¯ p\overline{p} , K + K − π + π −, π + π − π + π − and K + K − K + K − decay modes and the ϕ(1020) in the K + K − decay mode. The decay B s 0 → J/ψϕ is used as a normalisation channel. Evidence is also reported for the decay B s 0 → η c π + π −, where the η c meson is reconstructed in the pp¯¯¯pp¯ p\overline{p} decay mode, using the decay B s 0 → J/ψπ + π − as a normalisation channel. The measured branching fractions are B(B0s→ηcϕ)=(5.01±0.53±0.27±0.63)×10−4,B(B0s→ηcπ+π−)=(1.76±0.59±0.12±0.29)×10−4,B(Bs0→ηcϕ)=(5.01±0.53±0.27±0.63)×10−4,B(Bs0→ηcπ+π−)=(1.76±0.59±0.12±0.29)×10−4, \begin{array}{l}\mathrm{\mathcal{B}}\left({B}_s^0\to {\eta}_c\phi \right)=\left(5.01\pm 0.53\pm 0.27\pm 0.63\right)\times {10}^{-4},\hfill \\ {}\mathrm{\mathcal{B}}\left({B}_s^0\to {\eta}_c{\pi}^{+}{\pi}^{-}\right)=\left(1.76\pm 0.59\pm 0.12\pm 0.29\right)\times {10}^{-4},\hfill \end{array} where in each case the first uncertainty is statistical, the second systematic and the third uncertainty is due to the limited knowledge of the external branching fractions. Open image in new window
Im Titel werden "eta", "pi" und "phi" als griechische Buchstaben dargestellt
Im Titel ist "c" tiefgestellt
Im Titel sind "0" und "s" untereinander geschrieben: "s" ist tiefgestellt, "0" hochgestellt
Im Titel sind die Zeichen "plus" und "minus" hochgestellt
Gesehen am 26.10.2020